2017
DOI: 10.1017/s1463423617000330
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of Lebanese primary care physicians in nutrition counseling: a self-reported survey

Abstract: This is a descriptive study among a convenience sample of PCPs in Lebanon at two annual conferences in 2014 using an anonymous questionnaire. Findings Response rate was 54.6%. Overall, physicians considered that they have good to very good nutritional knowledge. Although they rated their formal nutritional education poorly, they had a positive attitude towards nutritional counseling and reported practicing general nutritional counseling with their patients. Barriers to nutritional counseling were: time, percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 19 publications
2
32
0
3
Order By: Relevance
“…Positive attitudes toward incorporating nutrition care in the management of patients living with diet-related chronic disease were found. This is consistent with other studies conducted around the world, which indicated that primary care physicians realise nutrition care as an important aspect of their clinical practice 14 19–21…”
Section: Discussionsupporting
confidence: 91%
“…Positive attitudes toward incorporating nutrition care in the management of patients living with diet-related chronic disease were found. This is consistent with other studies conducted around the world, which indicated that primary care physicians realise nutrition care as an important aspect of their clinical practice 14 19–21…”
Section: Discussionsupporting
confidence: 91%
“…However, additional training in topics such as motivational interviewing 229 seemed to increase motivation to provide nutrition care (50). In two studies, the authors interpreted PCPs' low motivation for nutrition care as a key factor contributing to the evidence-practice gap (39,40).…”
Section: Pcps' Motivation To Providing Nutrition Carementioning
confidence: 99%
“…Evidence exists that PCPs' nutrition guidance practices are not only determined by barriers (19,21,61,62,73,74,(78)(79)(80)(81)(82)(83)(84)(85)(86) but also by driving forces, self-efficacy factors and nutritional attitudes and beliefs, (21,23,34,61,62,66,68,70,72,73,(81)(82)(83)(85)(86)(87)(88)(89). In the studies reviewed, having a personal interest in nutrition (38,39,44), having healthy personal eating habits (46) and being a more experienced PCP (48,50) appeared to increase PCPs' perception of their nutrition capability 349 and motivation to provide nutrtion care (38,40,41). Early literature established that physicians with better personal health habits have more positive attitudes toward counseling (90).…”
Section: Increasing Pcp's Motivation To Provide Nutrition Carementioning
confidence: 99%
See 2 more Smart Citations